PENENTUAN KURVA RESPON SPECTRA GEMPA UNTUK WILAYAH JAKARTA - Andri Budiadi; Ambar Susanto (Jurnal Ilmiah Universitas Batanghari Jambi, 2009)
Probability Seismic Hazard Analysis (PSHA) has been applied in order to found the spectral response of the earthquake in Jakarta Region. All the possibilities of movement of the land as the result of the earthquake had analyzed integrated. N-value of SPT, Peak ground acceleration and others seismologists data had been used.The research shown that the Peak Acceleration of the Base Rock atJakartaregion is 0.185 g. The result according to a probability of 10%  of the design-age of 50 years at 500 years of period time.According to the result, the researchers propose the Acceleration of the peak soil at about 0.330 g for Jakarta Region. Kata kunci:Kurva Respon Spectra, wilayah gempa, Percepatan Puncak Batuan Dasar, Analisa Probabilitas